PHARMACOGNOSTICAL EVALUATION AND ANTIBACTERIAL ACTIVITY OF BARK OF Plumeria alba LINN. - SANGITA KUMARI; AVIJIT MAZUMDER; S.BHATTACHARYA (International Journal of Pharma and Bio Sciences, 2013)
In the present study the bark of Plumeria alba Linn. (Apocynaceae) was evaluated for pharmacognostical and phytochemical parameters and methanolic extract for antimicrobial activity by determining its MIC (by checker board method) and zone of inhibition (by cup plate method).Pharmacognostical parameters of the bark of Plumeria alba Linn. (Apocynaceae) were studied with the aim of drawing the pharmacopoeial standards for this species. The present study was also designed to evaluate the antimicrobial efficacy of the methanolic extract of the bark of Plumeria alba Linn. (Apocynaceae) against various diarrhea and dysentery causing drug resistant microorganisms isolated from patients admitted in hospitals. This study has pointed to the potential application of P. alba as a bactericide and fungicide.